2007
DOI: 10.1530/eje-07-0164
|View full text |Cite
|
Sign up to set email alerts
|

Influence of GH substitution therapy in deficient adults on the recurrence rate of hormonally inactive pituitary adenomas: a case–control study

Abstract: Objective: Several studies documented metabolic and psychological benefits of GH substitution in deficient adults, most of them suffering from benign pituitary adenomas. Since GH substitution is considered to promote tumour regrowth, adequate treatment is performed with some reservation. Therefore, we aimed to elucidate the effect of GH replacement therapy on tumour recurrence following surgery. Methods: In patients with hormonally inactive pituitary adenomas undergoing tumour surgery, a retrospective case-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 23 publications
4
28
1
2
Order By: Relevance
“…Out of the 55 matched pairs, there were 16 tumour progressions in the GH treatment group and 12 in the control group (69). Statistical analysis revealed no significant increase in either recurrence (PZ0.317) or progression (PZ0.617) within the follow-up period of 5 years (69). Therefore, in conclusion, available data do not suggest that GH replacement increases tumour recurrence or regrowth in adults, although further and larger studies are still needed.…”
Section: Hypothalamic-pituitary Tumoursmentioning
confidence: 77%
See 2 more Smart Citations
“…Out of the 55 matched pairs, there were 16 tumour progressions in the GH treatment group and 12 in the control group (69). Statistical analysis revealed no significant increase in either recurrence (PZ0.317) or progression (PZ0.617) within the follow-up period of 5 years (69). Therefore, in conclusion, available data do not suggest that GH replacement increases tumour recurrence or regrowth in adults, although further and larger studies are still needed.…”
Section: Hypothalamic-pituitary Tumoursmentioning
confidence: 77%
“…This selection included eight cases of central nervous system or pituitary tumours, four during administration of placebo and four during administration of GH. In a later case-control study, the treatment group comprised patients from the German KIMS database, and the control group comprised patients who had never been exposed to GH therapy (69). Out of the 55 matched pairs, there were 16 tumour progressions in the GH treatment group and 12 in the control group (69).…”
Section: Hypothalamic-pituitary Tumoursmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional characteristics of the included studies are shown in Table 1. As shown in table, seven of the selected studies obtained seven or more scores, which indicated that the study quality was relatively higher [5][6][7][14][15][16][17][18][19][20][21][22]; whereas, other studies with relatively lesser scores were considered of lower quality [23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies [5,19,20,22] assessed the relationship between GHRT and risk of recurrence/progression in pituitary adenomas. The cumulative estimated risk associated with GH use was 0.85 (95 % CI 0.65-1.11; I 2 = 16.6 %, p for heterogeneity = 0.309).…”
Section: Ghrt For Pituitary Adenomasmentioning
confidence: 99%